قرآن حکیم کی روشنی میں رحمت ِالٰہی کا تصور: Concept of Mercy of Allah in the Light of Holy Quran - Dr. Zulfikar Ahmad; Dr. Hafiz Muhammad Waseem Abbas (International Research Journal of Arabic and Islamic Studies, 2024)
According to the Quranic point of view the attribute of mercy of Allah Almighty prevails over all other attributes. No matter how severely Allah Almighty treats man, in terms of purpose the good of man lies in it. In this sense, the aspect of mercy is also found in all the other attributes. If one studies deeply then every verse of Quran will prove a sight of mercy because, resultantly, the motive of every command of Allah will be for the betterment and success of human beings.